A model of innovation network formation. Issue 2 (3rd April 2017) - Paredes-Frigolett, Harold; Pyka, Andreas
Abstract: In the field of innovation and entrepreneurship, scholars have addressed the strategic question of how innovation networks can be formed mainly in a descriptive fashion. As a result, general models of innovation network formation are still missing in the literature. We contribute to filling this important gap by putting forth a first general model of innovation network formation. Distilled from several cases of innovation network formation, the model allows policymakers and practitioners to implement innovation network formation strategies that can be applied not only in developing and transition countries but also in developed countries.